2018
DOI: 10.1167/iovs.17-22438
|View full text |Cite
|
Sign up to set email alerts
|

Early Gene Expression Profile in Retinal Ganglion Cell Layer After Optic Nerve Crush in Mice

Abstract: In response to ONC, the expression of apoptotic genes was stimulated soon after crush. Atf3, Lcn2, and Tnfrsf12a might be key molecules responsible for RGC loss in glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 107 publications
2
21
0
Order By: Relevance
“…Atf3 was previously found to be significantly changed in ONC GCL [12]. This result was in accord with our results.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Atf3 was previously found to be significantly changed in ONC GCL [12]. This result was in accord with our results.…”
Section: Discussionsupporting
confidence: 93%
“…LCM is often used to study the expression of both minimally or abundantly expressed genes in different brain regions [5][6][7][8][9] and occasionally in retinas [10][11][12]. In our study, we adopted an optimal LCM protocol with single-cell sequencing to examine the early mRNA changes in RGCs in an optic nerve crush model.…”
Section: Discussionmentioning
confidence: 99%
“…Atf3 was previously found to be significantly changed in ONC RGC layer. 12 , 15 This was in accord with our results, and it also proved the reliability of our results. Atf3 was reported to be involved in axonal regeneration, because Atf3 expression was activated after crush, and axonal regeneration was enhanced in various types of neurons as a result.…”
Section: Discussionsupporting
confidence: 93%
“…LCM is often used to study the expression of both minimally or abundantly expressed genes in different brain regions 5 9 and occasionally in retinas. 10 12 In our study, we adopted an optimal LCM protocol with microsequencing to examine the early mRNA changes in RGC layer in an optic nerve crush model.…”
Section: Discussionmentioning
confidence: 99%
“…While the majority of studies on the role of LCN-2 in ocular health focus on intraocular inflammation, a few studies demonstrated that LCN-2 is involved in a number of optic nerve disorders. For example, LCN-2 expression was increased > 80 fold in the ganglion cells following optic nerve crush-a popular model for glaucoma and neuronal apoptosis due to axonal degeneration [102]. LCN-2 was also found to regulate inflammation in the optic nerve during the progression of optic neuritis [103].…”
Section: Role Of Lcn-2 In Ocular Diseases: Focus On Age-related Maculmentioning
confidence: 99%